PEMODELAN TIME SERIES UNTUK NILAI TUKAR RUPIAH DI MASA PANDEMI COVID-19 - Hisyam Ihsan; Abdul Rahman; Sukarna Sukarna; Aswi Aswi; Muhammad Ammar Naufal (Math Program, Math and Science faculty, Pamulang University, 2022)
Abstract: Covid-19 is an international disaster with a long occurrence interval. The research divides this disaster into four phases, namely before the Covid-19 pandemic (1 January 2019 to 31 March 2020), the implementation of PSBB (1 April 2020 to 20 January 2021), the performance of PPKM & Micro-Lockdown (21 January 2021 to 23 July 2021), and after Covid-19 is reduced (24 July 2021 to 30 June 2022). Data on IDR to USD exchange rates were obtained from the official website from 1 January 2019 to 30 June 2022. Comparing the ARIMA temporal model for the four phases was proposed in this study as an inferential and descriptive way to compare exchange rates. The results showed that the IDR exchange rate against the USD closed at IDR 14,155.63 (before the pandemic), IDR 15,581.83 (PSBB period), IDR 14,362.84 (PPKM period), and IDR 14,368.16 (after the pandemic). According to the smallest AIC or parsimony considerations, the most effective ARIMA model is ARIMA(2,1,0) for the stage before the pandemic, ARIMA(0,2,1) for the stage during PSBB, ARIMA(3,1,0) for the stage during PPKM & micro-lockdown, and ARIMA(2,1,0) for the stage after the pandemic.ABSTRAK: Pandemi Covid-19 merupakan bencana internasional yang sangat panjang interval kejadiannya. Penelitian ini membagi bencana ini menjadi 4 fase, yaitu sebelum pandemi Covid-19 (1 januari 2019 s/d 31 Maret 2020), pemberlakuan PSBB (1 April 2020 s/d 20 Januari 2021), pemberlakuan PPKM & Micro-Lockdown (21 Januari 2021 s/d 23 Juli 2021), dan setelah Covid-19 berkurang (24 Juli 2021 s/d 30 Juni 2022). Data nilai tukar IDR ke USD diambil dari situs resmi mulai 1 Januari 2019 s/d 30 Juni 2022. Tujuan penelitian ini adalah membandingkan nilai tukar secara deskriptif dan inferensial dengan membandingkan model temporal ARIMA untuk keempat fase tersebut. Hasil penelitian menunjukan bahwa nilai tukar IDR terhadap USD ditutup pada Rp 14.155,63 (sebelum pandemi), Rp 15.581,83 (masa PSBB), Rp 14.362,84 (masa PPKM), dan Rp 14.368,16 (setelah pandemi). Model ARIMA terbaik berdasarkan AIC terkecil atau pertimbangan parsimony untuk tiap fase adalah ARIMA(2,1,0) sebelum pandemi, ARIMA(0,2,1) dimasa PSBB, ARIMA(3,1,0) dimasa PPKM & micro-lockdown, dan ARIMA(2,1,0) setelah masa pandemi.Kata kunci: covid-19, nilai tukar rupiah, model temporal, ARIMA.